L-Citrulline Influences the Body Temperature, Heat Shock Response and Nitric Oxide Regeneration of Broilers Under Thermoneutral and Heat Stress Condition - Uyanga, Victoria A.; Wang, Minghui; Tong, Tian; Zhao, Jingpeng; Wang, Xiaojuan; Jiao, Hongchao; Onagbesan, Okanlawon M.; Lin, Hai (Frontiers in Physiology, 2021)
Heat stress adversely affects several physiological responses in organisms, but the underlying molecular mechanisms involved are yet to be fully understood. L-Citrulline (L-Cit) is a nutraceutical amino acid that is gaining research interest for its role in body temperature regulation and nitric oxide synthesis. This study investigated whether dietary supplementation with L-Cit (1% of basal diet) could ameliorate the effects of acute heat stress on thermotolerance, redox balance, and inflammatory responses of broilers. Ross 308 broilers (288 chicks) were subjected to two environments; thermoneutral at 24 °C (TNZ) or heat stress at 35 °C for 5h (HS), and fed two diets; control or L-Cit. The results showed that HS increased the ear, rectal (RT), and core body (CBT) temperatures of broilers, along with higher respiratory rate. The RT and CBT readings were intermittently affected with time effect, whereas, L-Cit supplementation lowered the mean CBT than the control diet. Antioxidant assays showed that superoxide dismutase was increased during HS, while, catalase was promoted by L-Cit supplementation. In addition, L-Cit induced glutathione peroxidase activity compared to the control diet during HS. Hypothalamic heat shock protein (HSP)-90 was upregulated by HS, but L-Cit downregulated heat shock factor (HSF)-1, and HSP 60 mRNA expressions. HSF 3 mRNA expression was downregulated by L-Cit under TNZ condition. More so, HS increased the plasma nitric oxide (NO) concentration but lowered the total NO synthase (tNOS) activity. In contrast, L-Cit supplementation limited NO production but increased the tNOS activity. Arginase activity was increased in the control fed group during HS but L-Cit supplementation lowered this effect. The NOS-COX pathway was significantly affected under TNZ condition, since L-Cit supplementation downregulated the mRNA expression of iNOS-COX2 in the hypothalamus, and further reduced the serum PGE2 concentration. Together, these data indicates that L-Cit influenced the antioxidant defense, heat shock response and nitric oxide regeneration both under thermoneutral and HS conditions; and that L-Cit may be directly and/or indirectly involved in the central regulation of body temperature.